The Role of Lipid Environment in Ganglioside GM1-Induced Amyloid β Aggregation - Rudajev, Vladimir; Novotny, Jiri (Membranes, 2020)
Ganglioside GM1 is the most common brain ganglioside enriched in plasma membrane regions known as lipid rafts or membrane microdomains. GM1 participates in many modulatory and communication functions associated with the development, differentiation, and protection of neuronal tissue. It has, however, been demonstrated that GM1 plays a negative role in the pathophysiology of Alzheimer's disease (AD). The two features of AD are the formation of intracellular neurofibrillary bodies and the accumulation of extracellular amyloid β (Aβ). Aβ is a peptide characterized by intrinsic conformational flexibility. Depending on its partners, Aβ can adopt different spatial arrangements. GM1 has been shown to induce specific changes in the spatial organization of Aβ, which lead to enhanced peptide accumulation and deleterious effect especially on neuronal membranes containing clusters of this ganglioside. Changes in GM1 levels and distribution during the development of AD may contribute to the aggravation of the disease.
Keywords: amyloid β; GM1; gangliosides; Alzheimer’s disease; membrane microdomains; amyloid oligomers; fibrils